2020
DOI: 10.1101/2020.07.02.20145102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methodological Rigor in COVID-19 Clinical Research – A Systematic Review and Case-Control Analysis

Abstract: Objective: To systematically evaluate the quality of reporting of currently available COVID-19 studies compared to historical controls. Design: A systematic review and case-control analysis Data sources: MEDLINE, Embase, and Cochrane Central Register of Controlled Trials until May 14, 2020 Study selection: All original clinical literature evaluating COVID-19 or SARS-CoV2 were identified and 1:1 historical control of the same study type in the same published journal was matched from the previous year D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, there is no evidence to support that most fast-tracked studies from 2020 have been wasteful and aimed at self-promotion [2]. Notwithstanding, COVID-19 studies were found to be of worse quality than their prepandemic counterparts [10][11][12][13] and that is an indication that the reward system in science could have been currently skewed towards recognition at the expense of reliability [2]. On the topic of incentives and recognition, it is worthy mentioning that citation is not a reliable proxy for quality assessment.…”
Section: The Appeal Of Press Releases/conferences To Scientistsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, there is no evidence to support that most fast-tracked studies from 2020 have been wasteful and aimed at self-promotion [2]. Notwithstanding, COVID-19 studies were found to be of worse quality than their prepandemic counterparts [10][11][12][13] and that is an indication that the reward system in science could have been currently skewed towards recognition at the expense of reliability [2]. On the topic of incentives and recognition, it is worthy mentioning that citation is not a reliable proxy for quality assessment.…”
Section: The Appeal Of Press Releases/conferences To Scientistsmentioning
confidence: 99%
“…Accelerated time from submission to publication [6][7][8] and qualitative changes in the peer review processes [9] could imply lower quality of peer review in COVID-19 research. Evidence of lower quality of studies during the pandemic has indeed been found [2,[10][11][12]. Meanwhile, data availability practices remained largely unchanged, making claims still very hard to be independently verified [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be a few years though before being able to analyze the retraction rate of COVID-related papers 5 by means of comparing it with a control group. Yet, the time from article submission to online publication of COVID-related articles accelerated remarkably in comparison to previous publication timeframes according to independent studies published in pre-print servers and in prestigious journals as well [6][7][8][9][10] . For example, two independent studies found that the median time to final acceptance was eight times faster for COVID-related articles as opposed to papers on other issues [8][9] .…”
Section: Editorialmentioning
confidence: 99%
“…Yet, the time from article submission to online publication of COVID-related articles accelerated remarkably in comparison to previous publication timeframes according to independent studies published in pre-print servers and in prestigious journals as well [6][7][8][9][10] . For example, two independent studies found that the median time to final acceptance was eight times faster for COVID-related articles as opposed to papers on other issues [8][9] . One of them found that the median time from article receipt to article being made available online was five times faster for COVID-related articles as opposed to papers on other issues and more than 10% of COVIDrelated studies were found to had been accepted within two days after submission in a pool of PubMed-indexed journals which have had their metadata analyzed 9 .…”
Section: Editorialmentioning
confidence: 99%